2022
DOI: 10.7150/ijms.71971
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms based on lactate dehydrogenase to albumin ratio for predicting survival in colorectal cancer

Abstract: Purpose:We aimed to determine if lactate dehydrogenase to albumin ratio (LAR) might play a prognostic role for patients with operable colorectal cancer (CRC). Patients and Methods: 1334 operable CRC patients in Wuhan Union Hospital Between July 2013 and September 2017 were enrolled in this study and were randomly appointed them into training (n=954) and validation (n=380) sets. The relationship between LAR and overall survival (OS) and disease-free survival (DFS) were determined by restricted cubic splines (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“… 33 Thereafter, the prognostic significance of the LAR was validated in nasopharyngeal carcinoma, 34 , 35 gastric cancer, 36 and colorectal cancer. 37 , 38 In line with previous findings, our study provided additional evidence that the LAR could serve as an independent prognostic parameter in UCB, and the addition of the LAR to the prognostic nomograms would increase the predictive accuracies and clinical utilities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 33 Thereafter, the prognostic significance of the LAR was validated in nasopharyngeal carcinoma, 34 , 35 gastric cancer, 36 and colorectal cancer. 37 , 38 In line with previous findings, our study provided additional evidence that the LAR could serve as an independent prognostic parameter in UCB, and the addition of the LAR to the prognostic nomograms would increase the predictive accuracies and clinical utilities.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that the cutoff value of the LAR varied across studies. Different cutoff values of LAR were determined, including 5.5, 31 , 33 6.54, 32 4.04, 34 4.5, 37 4.91 38 and 3.67. 35 In our study, this value was 3.8.…”
Section: Discussionmentioning
confidence: 99%
“…Gan W and Peng RR et al concluded that LAR was a valuable independent factor in radically resected hepatocellular carcinoma and nasopharyngeal carcinoma [22][23]. Similarly, studies demonstrated that the prognostic value of LAR in esophageal squamous cell carcinoma and colorectal cancer [21,[24][25]. Moreover, LAR was superior to the tumor node metastasis stage for predicting OS and DFS [25].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, studies demonstrated that the prognostic value of LAR in esophageal squamous cell carcinoma and colorectal cancer [21,[24][25]. Moreover, LAR was superior to the tumor node metastasis stage for predicting OS and DFS [25]. However, the effect of LAR on GC was less well reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation